Development of Scratch-Based Srikandi Media for Indonesian Cultural Heritage in Elementary School: A Preliminary Study - Salzabila, Putri Alicia; Fakhriah, Fina; Fajrie, Nur (Jurnal Pijar Mipa, 2025)
This research aims to develop Scratch-based learning media called SRIKANDI on IPAS material for grade IV elementary school, especially Chapter 6, "Indonesia Cultural Heritage". This media is designed to increase student motivation, engagement and understanding of the material through an interactive technology approach. The research used the Research and Development (R&D) method with a model of ADDIE (Analysis, Design, Development, Implementation, Evaluation). This research is limited only to the analysis stage. The data collection techniques are questionnaires, observations, interviews and relevant literature studies. The population in this study is SD 4 Gulang. The participants in this study were 21 fourth-grade students and teachers. Data were analyzed using descriptive analysis. The results of this study showed that the learning media used are still limited to handbooks and worksheets, and the use of interactive multimedia is only limited to PowerPoint. Hence, it is necessary to develop interactive multimedia on IPAS material, especially Indonesia’s Cultural Heritage material, that suits the needs of students to achieve learning objectives. Based on this, it can be concluded that interactive multimedia with a contextual approach needs to be developed in IPAS subjects. Based on this, it can be concluded that interactive multimedia with a contextual approach needs to be developed in IPAS subjects.